Influência da nanoargila no envelhecimento higrotérmico de compósitos de polipropileno / PP maleado / fibra de vidro - Motezuki, Joice Erica (Universidade Federal de São Carlos, 2010)
In short glass fiber (GF) reinforced polypropylene (PP) composites, despite of the chemically inert and non-polar nature of the matrix, the fiber-matrix interfacial integrity may be compromised in a hygrothermal active environment by the addition of maleic anhydride (MAH) molecules of the interfacial compatibilizer (PP-g-MAH). The use of organophilic nanoclay particles (O-MMT, Cloisite 20A) could contribute to minimize this hygrothermal deterioration, due to its moisture barrier properties. So, the main goal of this study was to analyze the influence of O-MMT on the long-term mechanical performance of PP/PP-g-MAH/GF composites under hygrothermal ageing. Several PP composite formulations with constant GF content (40wt%) and varying concentrations of nanoclay (0.5; 1; 2; and 5wt%) were compounded in a corotating twin-screw extruder. The degree of nanoclay particles intercalation/exfoliation was characterized by X-ray diffraction (WAXD) and SEM/TEM microscopy analysis. Short-term mechanical characterization was carried out through standard tensile and Izod impact tests on injection moulded specimen. From this results, certain specimen were subjected to hygrothermal ageing in hot water at 80 ºC for 240/480/720 hours and the evolution of the hygrothermal deterioration was monitored by tensile tests. The increasing O-MMT content in unaged PP/PP-g-MAH/40%GF composites had an unexpected negative influence on short-term mechanical properties. Mechanical damping data indicated higher Tan  values for the ternary composite (PP/PP-g-MAH/40%GF/2%O-MMT), in comparison to the binary composite (PP/PP-g-MAH/40%FV), demonstrating deleterious effect of O-MMT on the fiber-polymer interfacial adhesion. SEM microscopy analysis of cryofractured surfaces were decisive for visual elucidation of the erosive action of O-MMT particles on the GF sizing treatment. Consequently, the relative tensile strength (TS) of the hygrothermally aged composite, with respect to that of the unaged composite (TSenv./TSn-env.), indicated that the addition of nanoclay in the ternary composite contributed to a higher deterioration of the long-term mechanical performance of GF-reinforced PP composites.
Influence of nanoclay on the hygrothermal ageing of polypropylene / maleated pp / glass fiber composites abstract
Keywords: Engenharia de materiais; Compósitos poliméricos; Envelhecimento higrotérmico; Propriedades mecânicas; Compatibilidade interfacial; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA